ECOLOGY OF FUTURE TEACHERS OF CHEMISTRY PREPARATION FOR IMPLEMENTATION OF EDUCATION (Scientific journal of the Fergana State University, 2023)
In this article, the issue of the importance of using new pedagogical methods, collaborative teaching technologyand working in small groups aimed at preparing future chemistry teachers to implement environmental education inchemistry teaching is analyzed. According to him, the article discusses the importance of using collaborative teaching inorder to improve the methodological preparation of future chemistry teachers in teaching chemistry.